Pendampingan Pemanfaatan Teknologi Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 di SMP Negeri 1 Sekongkang - Rizanty (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
In the era of the Covid-19 Pandemic, it demands massive changes in lifestyles in all levels of society in each of their respective environments. Included in the teaching and learning process that must be done online (in the network) through online learning media. The change in the learning system from the conventional to the online system was very sudden and without sufficient preparation, it caused the unpreparedness of teachers and students for the online learning process. However, all of this must be carried out so that the learning process can run smoothly and students actively participate in the Covid-19 pandemic. As a result of this emergency condition, an effort was made to help teachers by assisting the use of technology in online learning design at SMP Negeri 1 Sekongkang during the Covid-19 pandemic. The method in this research is PAR (Participation Action Research) where there are assisted subjects who are involved to jointly solve the problems that are being faced. The results obtained from this activity are very helpful for teachers in carrying out online learning by mastering the skills of using applications that support online learning. Activities can be carried out with adequate system support, but one obstacle is the instability of the internet network because activities are both online and offline